DIÁRIO DE BITITA: UMA ANÁLISE DA AUTOBIOGRAFIA DE CAROLINA MARIA DE JESUS SOB A PERSPECTIVA DO FEMINISMO NEGRO - Jorlaine Monteiro Girão de Almeida (2025)
This thesis aims to analyze the work Diário de Bitita, investigating how the narrative spaces traversed by the protagonist reveal experiences of violence, racial segregation, and social exclusion, especially from an intersectional perspective of gender, race, and class. The analysis begins with the understanding that literature produced by Black women in Brazil has historically been silenced by structural exclusions, and that the autobiographical writing of Carolina Maria de Jesus breaks with this pattern by transforming her lived experience into narrative resistance. Through a reflection on the principles of Black feminism and intersectionality, it may be possible to understand Carolina’s work as a political reading, connected to the power relations present in society. This is a bibliographic research project that involves literary and social analysis, drawing primarily on the theoretical foundations of the following authors: Philippe Lejeune (2008), Regina Dalcastagnè (2023), Germana Sousa (2004), Lélia Gonzalez (2020), Sueli Carneiro (2011), Winnie Bueno (2020), Françoise Vergès (2020), and Patricia Hill Collins (2019).